Technique for Adaptation of Konno Aortoventriculoplasty in Patient-Prosthesis Mismatch - Vural, Kerem M.; Sabuncu, Timucin (The Thoracic and Cardiovascular Surgeon, 2021)
The patient-prosthesis mismatch has been reported as an important cause of adverse outcome following aortic valve replacement. The relief of patient-prosthesis mismatch generally requires a reoperation of comprehensive nature, which necessitates an extensive aortic root enlargement. The Konno aortoventriculoplasty represents an efficient treatment option, as this technique provides both extreme root enlargement and relief of the frequently associated subvalvular obstruction. However, the application and conduct of the procedure may somewhat differ from the pediatric Konno procedures. This article describes our surgical technique adaptation in Konno-aortoventriculoplasty for adult patient-prosthesis mismatch cases, highlighting the differing points from the pediatric-Konno.
Keywords: aortic valve and root; heart valve surgery; reoperation